Incidence and economic burden of acute otitis media in children aged up to 5 years in three Middle Eastern countries and Pakistan: A multinational, retrospective, observational study. Issue 2 (June 2017) - Mustafa, Ghulam; Al Aidaroos, Amal Y.; Al Abaidani, Idris S.; Meszaros, Kinga; Gopala, Kusuma; Ceyhan, Mehmet; Al-Tannir, Mohamad; DeAntonio, Rodrigo; Bawikar, Shyam; Schmidt, Johannes E.
Abstract: Epidemiological data on acute otitis media (AOM), an infectious disease frequently affecting children, are lacking in some countries. This study was undertaken to assess the incidence of AOM in children ≤5 years in Saudi Arabia, Oman, Pakistan, and Turkey, as well as the economic burden from a parent/caregiver perspective. Medical records of 4043 children (Saudi Arabia = 1023, Oman = 998, Pakistan = 1022, Turkey = 1000) were retrospectively reviewed and the incidence of AOM episodes calculated from suspected and confirmed cases. Using a standardized Health Economics Questionnaire, parents recorded resource use and expenses incurred per AOM episode [in local currency and converted to US dollars (USD)]. The overall incidence of AOM episodes per 1000 person–years was: Saudi Arabia, 207 [95% confidence interval (CI): 178–238]; Oman, 105 (95% CI: 85–127); Pakistan, 138 (95% CI: 116–163); and Turkey, 99 (95% CI: 79–123). The mean total out-of-pocket healthcare expense incurred by parents/caregivers per episode was: Saudi Arabia USD67.1 [standard deviation (SD) = 93.0], Oman USD16.1 (SD = 16.4), Pakistan USD22.1 (SD = 20.5), and Turkey USD33.6 (SD = 44.9). The incidence of AOM episodes varied across all four countries, probably due to different diagnostic and management practices. Nevertheless, our results confirm that AOM causes a substantial burden to public health, reinforcing the need for cost-effective prevention strategies.